Modifying Non-communicable Disease Behaviours through Effective Health Communication and Behaviour Change: A Systematic Review - Tejaswini B. Darukaradhya; J. Krishnamurthy (Preventive Medicine: Research & Reviews)
Non-communicable diseases (NCD) account for 74% of global mortality. Approximately 86% of all premature deaths occur in low- and middle-income countries majorly attributed to lifestyle changes or behavioural risk factors. The theory-based behaviour change interventions (BCIs) appear promising, but their applicability is not explored within the national programmes. The current paper aims to review the effectiveness of theory-based BCI in modifying the NCD risk factors and provide insights into the national NCD programmes. Interventions conducted to evaluate theory-based BCIs between 2002 and 2022 in modifying behavioural risk factors for NCDs were identified from multiple databases (PubMed, Scopus, Google Scholar and Cochrane Library) for systematic review. The final analysis included 35 studies that used theories and models that broadly come under one of the four approaches, i.e. intrapersonal (targets inherent individual factors for behaviour change), interpersonal (targets the family or groups), community (target socio-cultural ecosystems) and integrated (combination of other three approaches). Twenty-seven studies showed significant results. The highest number of studies were of interpersonal approach using socio-cognitive theory and integrated (11 each), and strength of evidence was moderate for both. Twenty-six studies focused on physical inactivity and unhealthy diet. The review supports the effectiveness of behaviour change interventions for mitigating NCD risk factors. Further efforts, including implementation research study methods, should be directed to evaluate effects of these interventions on population health outcomes within specific cultural and social contexts.